The contribution of (shadow) banks and real estate to systemic risk in China - Bellavite Pellegrini, Carlo; Cincinelli, Peter; Meoli, Michele; Urga, Giovanni (Journal of Financial Stability, 2022)
We empirically evaluate how accounting and financial variables affect the level of systemic risk in traditional and shadow banks, and in real estate finance services in China over the period 2006–2019. We also conduct some stability analysis by evaluating the impact of crisis sub-periods. We find that systemic risk increases in the Size of large financial institutions, particularly shadow entities, while it is insensitive to the Size of real estate finance services. Real estate finance services are instead particularly sensitive to Maturity Mismatch and Leverage. Finally, systemic risk differs across state and non state owned banks.